Answers

2015-10-04T18:13:53+08:00
     2                 4     
 a + 3           a - 3

Factor the denominators. (The given denominators are already on their factored form so we'll just copy them).
a + 3 = a + 3
a - 3 = a - 3

Let's construct their LCD.
LCD = (a + 3)(a - 3)

Rewrite each rational expression with the LCD as denominator.
     2                 4        =       2 (a - 3)               4 (a + 3)    
  a + 3           a - 3          (a + 3)(a - 3)         (a + 3)(a - 3) 

We get 2(a - 3) and 4(a + 3) from dividing the LCD to their factored denominators then multiply them to their numerator.
(a + 3)(a - 3)   =   a - 3
    a + 3

(a + 3)(a - 3)   =   a + 3
    a - 3

Now do the indicated operation.
    2 (a - 3)   -     4 (a + 3)      =      2 - 4              
          (a + 3)(a - 3)                          1
                                              =      -2    
                                                       1
                                              =    -2

That's it. Hope you understand it! :)
                                                                                  -KookEin
Note: It's not copied :)
0